(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A variety of amino acids and aldehydes or ketones are employed in a condensation process toproduce schiff bases, which are useful chemical molecules. These ligands are regarded as favored sincethey may be easily produced via condensation. As an O2 detector, they have a variety of applications inthe fields of medicine and pharmacology coordination chemistry biological activities food packagingdyes and polymer. Imine derivative semicarbazone is formed via the condensation of semicarbazide and asuitable ketone or aldehyde with the imine group. Transition metal complexes including copper, zinc,and cadmium are good precursors for the production of metal or metal chalcogenide nanoparticlesbecause they contain Imine ligands. Due to multiple applications in pharmacology such as antiviral,antifungal, antibacterial, antimalarial, antituberculosis, cancer-fighting, anti-HIV, catalytic oxidation oforganic molecules and nanotechnology, researchers have focused a great deal of their attention onSchiff bases in recent years. In this paper review the application, structure and properties of some schiffbase metal complexes.